Electronic Management and its Role in Improving Administrative Work in Public Schools in Al Buraimi and Al Dhahirah, Sultanate of Oman - Al-karusi, Zaid Khamis Ali; Aldaba, Abdulmajid Mohammed; Bin Ibrahim, Mohd Burhan (Journal of Educational and Psychological Sciences, 2021)
The study aimed to find out the role of electronic management in improving administrative work in government schools in Buraimi Region and Al Dhahirah Region in Oman based on principals and their deputies' perspectives. The descriptive analytical design was used to analyse the data and answer the questions of the study.Researchers developed a questionnaire consisting of (55) items which were divided into two parts: availability of electronic management requirements, and administrative work. The sample consisted of (111) school principals and their deputies. The outcomes showed that the degree of availability of requirements for the application of electronic in public schools in both regions was on the average (medium) level (3.28 out of 5). More specifically, the outcomes revealed that the availability of materialistic requirements has got (3.55) which is considered 'high'. |Second, human and technical requirements have got (3.36); and thirdly, rules and regulations have got (3.16). Finally, the financial requirements have got an average level of (2.98).The outcomes have also shown that the electronic management has a role in improving administrative work with an average level (4.01) which is considered high. In terms of the fields in this part, the organization has got the highest average (4.11); planning has got an average of (4.01); supervision has got an average of (3.98); directions have got an average of (3.97); and finally, the decision-making has got an average of (3.94).In addition, the findings indicated that there is no statistically significant difference between the average responses of the study sample about the role of electronic management in improving administrative work due to the 'years of experience' variable. The study recommended allocating an appropriate budget for public schools in Oman to provide the necessary requirements (computers) and maintenance to apply electronic management effectively.
Keywords: electronic management; improving administrative work; Public schools; Sultanate of Oman